Autofertility and self‐compatibility moderately benefit island colonization of plants. Issue 3 (25th December 2018) - Razanajatovo, Mialy; van Kleunen, Mark; Kreft, Holger; Dawson, Wayne; Essl, Franz; Pergl, Jan; Pyšek, Petr; Winter, Marten; Weigelt, Patrick
Abstract: Aim: The current geographical distribution of species largely reflects colonization success after natural long‐distance dispersal or introduction by humans. Plants with selfing ability should have an advantage when establishing on islands where mates and pollinators are limited (Baker's law). However, high percentages of dioecious and self‐incompatible species have been reported for some islands, possibly resulting from post‐colonization evolution. Given that such evolution is less likely to apply to alien species recently introduced to islands by humans, tests of Baker's law on islands need to consider both native and naturalized alien species. Location: Global. Time period: Undefined. Major taxa studied: Angiosperms. Methods: To test whether the colonization of islands is associated with selfing ability (self‐compatibility and autofertility), we combined three comprehensive global databases: one on breeding systems of species, one on island and mainland distributions of native species and one on global naturalization of alien plants. We assigned each of a total of 1, 752 species, from 161 angiosperm families, as mainland species, island colonists and/or island endemics (i.e., species that are restricted to islands). To assess potential relationships between island occurrence and selfing ability of species, we used multinomial logistic regressions. Results: We found that species with high selfing ability were slightly more likely to be island colonist than mainland species. However, selfing ability did not increase the likelihood of being an island endemic in contrast to mainland species. Among island colonists, selfing ability did not differ between species on oceanic and on continental islands or between species native to islands and naturalized on islands. Main conclusions: We performed a comprehensive test of Baker's law by considering many angiosperm families, using continuous metrics of self‐compatibility and autofertility and including both native and naturalized species. We provide global evidence that high selfing ability may foster island colonization of angiosperms.